2015
DOI: 10.3109/00952990.2014.985829
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities in long-term heroin users: a preliminary neuroimaging meta-analysis

Abstract: These preliminary findings suggest that heroin abuse is significantly associated with damage to white matter integrity. These results are considered preliminary and analyses should be revisited with more primary studies focusing on either long- or short-term abuse as well as abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…In addition to increased BBB permeability, experimental studies have found that even a single acute exposure to methamphetamine causes profound CBF reductions [175]. Also, recent preliminary studies have found that heroin use leads to microvascular damage and microcirculation dysfunction, collapse and fracture of the myelin sheath and vacuole formation in white matter regions around microvessels, as identified in post-mortem human brain tissue [176,177]. …”
Section: Vascular Risk Factors Lifestyle and Environmentmentioning
confidence: 99%
“…In addition to increased BBB permeability, experimental studies have found that even a single acute exposure to methamphetamine causes profound CBF reductions [175]. Also, recent preliminary studies have found that heroin use leads to microvascular damage and microcirculation dysfunction, collapse and fracture of the myelin sheath and vacuole formation in white matter regions around microvessels, as identified in post-mortem human brain tissue [176,177]. …”
Section: Vascular Risk Factors Lifestyle and Environmentmentioning
confidence: 99%
“…Specifically, dysfunction of the fronto-subcortical circuitry, namely connectivity of prefrontal cortex and ventral striatum, has been consistently linked with the development and maintenance of addiction (Everitt & Robbins, 2013;Koob & Volkow, 2010). Indeed, significant reductions in white matter integrity of major frontal and interhemispheric tracts are reliably observed in stimulant users (London, Kohno, Morales, & Ballard, 2015;Romero, Asensio, Palau, Sanchez, & Romero, 2010), opioid users (Wollman et al, 2015), alcohol users (Fortier et al, 2014), and polysubstance users (Unterrainer et al, 2015) compared to healthy controls. Moreover, longer duration of substance use is correlated with poorer white matter integrity (Ersche et al, 2012;Fortier et al, 2014;Wollman et al, 2015).…”
Section: Secondary Analysesmentioning
confidence: 99%
“…Indeed, significant reductions in white matter integrity of major frontal and interhemispheric tracts are reliably observed in stimulant users (London, Kohno, Morales, & Ballard, 2015;Romero, Asensio, Palau, Sanchez, & Romero, 2010), opioid users (Wollman et al, 2015), alcohol users (Fortier et al, 2014), and polysubstance users (Unterrainer et al, 2015) compared to healthy controls. Moreover, longer duration of substance use is correlated with poorer white matter integrity (Ersche et al, 2012;Fortier et al, 2014;Wollman et al, 2015). Fronto-subcortical circuitry has also been implicated in a range of major psychiatric conditions such as schizophrenia and depression (Pujara & Koenigs, 2014), and white matter deficits are found to correlate with illness severity (Lagopoulos et al, 2013).…”
Section: Secondary Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to healthy controls, significant white matter alterations in major frontal and interhemispheric tracts are reliably observed in users of stimulants (London, Kohno, Morales, & Ballad, ; Romero, Asensio, Palau, Sanchez, & Romero, ), opioids (Wollman et al, ), alcohol (Fortier et al, ), and polysubstances (Unterrainer et al, ), with longer durations of substance use correlated with greater white matter deficits (Ersche et al, ; Fortier et al, ; Wollman et al, ). Extensive white matter abnormalities have also been reported in schizophrenia (Ellison‐Wright & Bullmore, ; Samartzis, Dima, Fusar‐Poli, & Kyriakopoulos, ) and HIV infection (Holt, Kraft‐Terry, & Chang, ; Leite et al, ).…”
Section: Introductionmentioning
confidence: 99%